(2x-7)(6x+7)=0

Simple and best practice solution for (2x-7)(6x+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-7)(6x+7)=0 equation:



(2x-7)(6x+7)=0
We multiply parentheses ..
(+12x^2+14x-42x-49)=0
We get rid of parentheses
12x^2+14x-42x-49=0
We add all the numbers together, and all the variables
12x^2-28x-49=0
a = 12; b = -28; c = -49;
Δ = b2-4ac
Δ = -282-4·12·(-49)
Δ = 3136
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{3136}=56$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-28)-56}{2*12}=\frac{-28}{24} =-1+1/6 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-28)+56}{2*12}=\frac{84}{24} =3+1/2 $

You can always share this solution

See similar equations:

| 3x-2/3x=3/14 | | 48p=12 | | 0=-4.9t^2+9.8t | | -11-x=-17 | | 48÷p=12 | | 14x-1=-57 | | 9*x+1/7=18 | | 5x-2=-4x+12 | | 14x–61=2x+35 | | 2x+35=14x–61 | | 134=5x+84 | | 5(x-5)-x=4x | | 67=5x+84 | | x+34=11x-56 | | x-26=x+37 | | 9p?2=?10p-2 | | 8b-7=17 | | 5x+16=7×-14 | | 3y=5-6 | | 6r-5=8r-23 | | 4+15x=-1 | | -2-8x-9=-9x-10 | | 5–10=5(x–2) | | 5x=7=73 | | -3-4y=20 | | X+3(x/2)+90=180 | | (12,3)m=-4 | | 0.12x=23270 | | -8p-11=-43 | | 2x-10=72 | | 4r=-5r+9r | | (3x-5)(x-2)(x+1)=0 |

Equations solver categories